KARAKTER DAN PEMAHAMAN PENDIDIKAN KARAKTER MAHASISWA PENDIDIKAN AKUNTANSI MELALUI PEMBELAJARAN STRATEGI BELAJAR MENGAJAR BERKARAKTER - Santoso, Jarot Tri Bowo (Fakultas Ekonomi, Universitas Negeri Semarang, 2013)
The objectives of the study were to understand (1) studentsâ understanding about character education after joining the class of teaching-learning strategy of character Accounting, (2) the characters of education students after joining the class of character Accounting. It was a class action research and the respondents were 53 Accounting Education students in the 5th semester. The study was done in 2 cycles. The data were collected by tests and observation and were analyzed by percentage descriptive. The result of study showed that: 1) Studentsâ understandings of character education increased 27% in the 1st cycle and 39% in the 2nd cycle. 2) The character average of education students was 82.2% in good category.Â